Psychological Capital, Work Happiness, and Innovative Behaviour: Evidence from Millennials Worker of Star-Rated Hotels - Indrayani, I Gusti Ayu Putu Wita; Sari, Desak Made Febri Purnama (Jurnal Ilmiah Manajemen & Bisnis, 2025)
This study focuses on the innovative behaviour of starred hotel employees driven by their psychological capital and happiness at work. An explanatory sequential analysis with a positivistic paradigm were applied through the Smart PLS approach. Data were collected through a cross-sectional survey of 129 millennial employees at starred hotels which were validated through in-depth interviews with different levels millennial employees. The findings of the study indicate that happiness at work fully mediates the effect of psychological capital on innovative work behaviour. Psychological capital offers psychological resources that enable employees to experience job happiness, which in turn fosters the development of innovative behaviour. Happiness at work creates an internal drive to try new things, participate in innovation efforts, and contribute to improving work processes. Several dimensions play an important role in the formation of innovation through work happiness, namely a positive work environment, career development opportunities and flexibility, work-family balance, recognition and appreciation. The practical implications of this study offer recommendations for star hotel management to enhance organizational culture that fosters employees’ happiness at workplace by implementing recognition and appreciation programs, providing work-life balance facilities, and strengthening positive work relationships. Theoretically, these findings align with the conservation of resources theory which is emphasizing the reinforcement of internal resources to support innovative work behaviour. Future research is encouraged to validate these findings in different contexts to enhance generalizability.